2024
DOI: 10.1111/tid.14227
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of valganciclovir‐related leukopenia and neutropenia in solid organ transplant recipients at high risk of cytomegalovirus disease

Sara Belga,
Cristina Hernandez,
Dima Kabbani
et al.

Abstract: BackgroundValganciclovir (VGCV) prophylaxis is associated with an increased risk of hematologic side effects. We analyzed the impact of VGCV prophylaxis on leukopenia and neutropenia rates and explored risk factors for its occurrence.MethodsRetrospective cohort study of adult cytomegalovirus (CMV)‐seronegative solid organ transplantation (SOT) recipients of either CMV‐seropositive (CMV D+/R‐) or CMV‐seronegative (CMV D‐/R‐) donors between July 2005 and March 2019. CMV D+/R‐ SOT recipients received 3–12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Studies in adult transplant recipients receiving valganciclovir 900 mg daily showed similar exposure to 5 mg/kg IV ganciclovir, the typical CMV prophylaxis dose, aiding the transition to enteral therapy [3]. However, reports of myelosuppression surfaced [3,4]. Pediatric dosing challenges arose, with initial weight-based regimens potentially causing under-exposure [5].…”
mentioning
confidence: 99%
“…Studies in adult transplant recipients receiving valganciclovir 900 mg daily showed similar exposure to 5 mg/kg IV ganciclovir, the typical CMV prophylaxis dose, aiding the transition to enteral therapy [3]. However, reports of myelosuppression surfaced [3,4]. Pediatric dosing challenges arose, with initial weight-based regimens potentially causing under-exposure [5].…”
mentioning
confidence: 99%